Bilateral ballism in a patient with overlapping Fisher's and Guillain-Barré syndromes - Odaka, M (BMJ Group, 1999)
A 29 year old woman developed diplopia and ataxic gait. Neurological examination showed total ophthalmoplegia, cerebellar ataxia, and areflexia. Moreover, there was muscle weakness in all four limbs. An overlap of Fisher's and Guillain-Barré syndromes was dignosed. On day 5 she suddenly developed involuntary flinging movements that affected the face and four limbs. Surface EMG showed 1.5-2 Hz rhythmic grouping discharges. The involuntary movements were considered ballism. This is the first report of a patient with Guillain-Barré syndrome and a related disorder who showed ballism.